Editorial: Regions in evolution. Transitions, renewal and emerging forms of regionalisation - Thomas Perrin (Belgeo)
This issue of Belgeo resumes the analysis of the region in geography and spatial planning, with regard to changes in existing regions and to the forms and methods of regionalisation that emerge at different scales, more or less informal or formalised. The issue begins with an epistemological review of the notion of region, in order to grasp both its complexity and its permanence in the field of geography and spatial planning, at conceptual and instrumental levels. Several corpuses and approaches to the region are combined to provide an interdisciplinary and international vision of the subject. The conclusions on the ‘state of the region’ today lead to renewed visions of the thinking and practice of regional planning, between the cooplexity of regional groupings and a post-complex approach to planning mechanisms.